Identification of Peptide Ligands for Targeting to the Blood-Brain Barrier - van Rooy, Inge (Springer US, 2010)
PURPOSE: Transport of drugs to the brain is limited by the blood-brain barrier. New, specific brain endothelium ligands can facilitate brain-specific delivery of drugs. METHODS: We used phage display in an in situ brain perfusion model to screen for new brain endothelium peptide ligands. RESULTS: Two phage clones, displaying 15 amino acid-peptides (GLA and GYR) that were selected for brain binding in the mouse model, showed significant binding to human brain endothelium (hCMEC/D3), compared to a random control phage. This binding was not seen for other human endothelial cells (HUVEC). Binding to hCMEC/D3 cells was dose dependent. When phage GLA and GYR were individually perfused through the murine brain, their ability to bind to the brain was 6-fold (GLA) and 5-fold (GYR) higher than the control phage. When compared to lung perfusion, phage showed an 8.5-fold (GYR) and 48-fold (GLA) preference for brain over lung compared to the control. CONCLUSIONS: These results indicate that two new peptide ligands have been identified that may be used for specific targeting of drugs to the blood-brain barrier.